APLIKASI PENJUALAN KUE KOYA BERBASIS WEB DENGAN METODE RAPID APPLICATION DEVELOPMENT (STUDI KASUS : UMKM KUE KOYA MAYASARI) - Yanuar Firmansyah, Tessa; Dwicahya Supriatman, Rian; Sidiq, Maulana (Jurnal Mahasiswa Sistem Informasi Galuh, 2024)
This research aims to design an online Koya cake sales website to support the Mayasari Koya Cake MSMEs using the Rapid Application Development (RAD) method, which allows for fast and adaptive software development. The website, designed to expand market reach and increase sales for Koya Mayasari Cake MSMEs, includes features such as product display, shopping basket, and online payment system. Despite limitations such as time and resource constraints for website design, further research can enhance website features and functionality, and evaluate its impact on sales and growth of Koya Mayasari Cake MSMEs.